Ubiquitous Motor Cognition in Musical Experience: Open Peer Review of Jacques Launay’s “Musical Sounds, Motor Resonance, and Detectable Agency” - Godoy, Rolf Inge (Empirical Musicology Review, 2015)
Motor cognition, defined as the capacity to conceive, plan, control, perceive, and imagine body motion, is here seen as an ubiquitous element in music: music is produced by body motion, people often move in various ways when listening to music, and images of body motion seem to be integral to mental images of musical sound. Given this ubiquity of motor cognition in musical experience, it could be argued that motor cognition is a fundamental element in music, and thus could be hypothesized to also have been an essential element in the evolution of music, regardless of whether music is seen as primarily a social or as a more solitary phenomenon. It could furthermore be argued that music in all cases has intersubjective significance because of shared motor cognition among people, and also that this motor cognition may be applied to most perceptually salient features of music.